2013
DOI: 10.4156/jnit.vol4.issue4.2
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of History Digital Game Based Learning (DGBL) Software

Abstract: The aim of this study was to design and evaluate a Digital Game Based Learning software for history subject. The methodology used was Instructional Design-Digital Game Based Learning (ID-DGBL) Model adapted from ADDIE and game development as well as 5E intructional models. Design elements include learning theories, pedagogy and game components. The effectiveness evaluation used quasi-experimental tecnique via pre and post tests. The samples involved were 60 secondary school students; 30 in experimental group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…In general, theory is useful to explain certain phenomenon which in this context is learning through digital games. However, some of the studies on educational digital games support the usefulness of the theory underpinning and guiding the overall look of the game design (Ahmad et al, 2015;Clark et al, 2015;Elsattar, 2017;Ishak et al, 2021;Kiili, 2005;Mat Zin & Wong, 2013;Pereira de Aguiar et al, 2018;Plass et al, 2015;Rooney, 2012;Sung et al, 2017;Taylor et al, 2017;Wu et al, 2012;Zaibon & Shiratuddin, 2010). Wu et al (2012) identified that there are four types of major learning theory used in educational digital games, namely behaviourism, cognitivism, humanism, and constructivism.…”
Section: The Need For Theorymentioning
confidence: 99%
“…In general, theory is useful to explain certain phenomenon which in this context is learning through digital games. However, some of the studies on educational digital games support the usefulness of the theory underpinning and guiding the overall look of the game design (Ahmad et al, 2015;Clark et al, 2015;Elsattar, 2017;Ishak et al, 2021;Kiili, 2005;Mat Zin & Wong, 2013;Pereira de Aguiar et al, 2018;Plass et al, 2015;Rooney, 2012;Sung et al, 2017;Taylor et al, 2017;Wu et al, 2012;Zaibon & Shiratuddin, 2010). Wu et al (2012) identified that there are four types of major learning theory used in educational digital games, namely behaviourism, cognitivism, humanism, and constructivism.…”
Section: The Need For Theorymentioning
confidence: 99%
“…success Game content is tested using t-test and GEQ (Game Engagement Questionnaire). T-test is used to find out the positive impact of this game on the user [17]. The engagement between game and user is calculated using GEQ [18].…”
Section: Quality Analysismentioning
confidence: 99%